LncRNA CASC9 regulates cell proliferation, apoptosis and cell cycle via sponging miR-145-5p in colon cancer cells - Sun, Guangyuan; Guo, Fei; Wu, Xueliang; Han, Lei; Xue, Jun (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: LncRNA cancer susceptibility candidate 9 (CASC9) is up-regulated in various cancers. In this study, we explored the role of CASC9 in colon cancer (CC). Methods: The level of CASC9 in CC tissues, adjacent normal tissues, intestinal epithelial cells (HIEC) and CC cell lines was evaluated by qRT-PCR. HCT116 and SW480 CC cells were transfected with siCASC9. The cell growth and cell proliferation makers (Ki-67 and PCNA) were detected by CCK-8, colony formation and western blotting, respectively. The cell apoptosis and cell cycle were determined by flow cytometry. MicroRNA sponged by CASC9 was predicted by starBase and verified by dual-luciferase reporter assay. Further analyses were performed to investigate the role of CASC9 sponging the microRNA in CC cells by transfection or co-transfection of siCASC9 and miR-145-5p inhibitor. Results: LncRNA CASC9 was high-expressed in CC cells and tissues, especially in CC at advanced TNM stages. In HCT116 and SW480 cells, knockdown of CASC9 suppressed cell proliferation, promoted cell apoptosis and arrested cell cycle at G0/G1 phase. Furthermore, CASC9 was observed to sponge and regulate the expression of miR-145-5p, which was down-regulated in CC tissues. Moreover, increased cell proliferation and decreased cell apoptosis and arrested cell cycle caused by miR-145-5p inhibitor were abrogated by the knockdown of CASC9. Conclusions: LncRNA CASC9 is an oncogene in CC cells through sponging miR-145-5p. The findings in the current study provide a new understanding on CASC9 in CC.